Developing and Proposing Zakat Management System: A Case of the Malakand District, Pakistan - Suhail Ahmad (International Journal of Zakat, 2019)
Zakat plays a vital role in the socio-economic development of a country. With zakat, the poor community is facilitated their food, safety, nutrition, sanitation, education, and other necessities. This study focuses on the role and current practice of zakat in the Malakand district of Khyber Pakhtunkhwa, Pakistan. This paper also develops and proposes a model for efficient management of zakat there. In doing so, this study interviews a sample of thirty respondents. A list of ten questions is constructed during the interviews using the local language, which is Urdu. The current practice of zakat in the region is explored, and further recommendation is captured for better practice of zakat management. For this, the study proposes an ideal model of the zakat management system, which can also be adopted by other countries. The discussion of this study is limited to the district of Khyber Pakhtunkhwa of Pakistan. Keywords: Zakat, poverty alleviation, socio-economic development, ideal management, Pakistan